Continuing education in the family health strategy: rethinking educational groups - Cinira Magali Fortuna; Silvia Matumoto; Maria José Bistafa Pereira; Celiane Camargo-Borges; Lauren Suemi Kawata; Silvana Martins Mishima (Universidade de São Paulo, 2013)
OBJECTIVE: to analyze the experience of the family health team in resignifying the way to develop educational groups. METHOD: groups of discussion, with twenty-six biweekly group meetings conducted, with an average of fifteen professionals from the family health team, during the year 2009. The empirical material consisted of the transcription of the groups, on which thematic analysis was performed. RESULTS: two themes were developed and explored from the collective discussions with the team: "The experience and coordination of the groups" and "The work process and educational groups in a service-school". CONCLUSIONS: continuing Education in Health developed with the team, not only permitted learning about the educational groups that comprised the population, but also contributed to the team's analysis of its own relationships and its work process that is traversed by institutions. This study contributed to the advancement of scientific knowledge about the process of continuing health education as well as educational groups with the population. Also noteworthy is the research design used, providing reflexivity and critical analysis on the part of the team about the group process experienced in the meetings, appropriating knowledge in a meaningful and transformative manner.